2014
DOI: 10.1007/s11695-014-1427-3
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal-Jejunal Bypass Restores Insulin Action and Βeta-Cell Function in Hypothalamic-Obese Rats

Abstract: DJB ameliorated glucose homeostasis, restored hepatic insulin action, and normalized islet function in HyO rats, indicating that this surgery may be useful for the treatment of hypothalamic obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
1
6
1
Order By: Relevance
“…Regarding the lipidic metabolism in MSG rats, although there are some discrepancies among our data on unmodified peripheral TG concentrations, it must be mentioned that other researchers found enhanced basal TG levels where they have taken those samples at 8 or more hours after food was withdrawn (fasting condition) [ 40 , 41 ]. When analyzing peripheral TG levels in response to LPS in MSG rats, it has been shown that MSG rats, over development, display reduced lipolytic and enhanced lipogenic activities [ 42 ], thus indicating that after the allostatic load (LPS injection) the balance of activities strongly support for the enhanced MSG AUC of this lipid [ 43 , 44 ].…”
Section: Discussioncontrasting
confidence: 59%
“…Regarding the lipidic metabolism in MSG rats, although there are some discrepancies among our data on unmodified peripheral TG concentrations, it must be mentioned that other researchers found enhanced basal TG levels where they have taken those samples at 8 or more hours after food was withdrawn (fasting condition) [ 40 , 41 ]. When analyzing peripheral TG levels in response to LPS in MSG rats, it has been shown that MSG rats, over development, display reduced lipolytic and enhanced lipogenic activities [ 42 ], thus indicating that after the allostatic load (LPS injection) the balance of activities strongly support for the enhanced MSG AUC of this lipid [ 43 , 44 ].…”
Section: Discussioncontrasting
confidence: 59%
“…This assumption is further supported by the fact that fasting serum insulin levels did not differ between the groups ( Table 2 ). Moreover, measurements of Akt phosphorylation at basal non-stimulated conditions have been reported by others [ 65 , 66 , 67 , 68 ]. Collectively, our data demonstrates that EA exerts anti-diabetic effects, consistent with previous findings [ 21 , 60 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 82%
“…DJB surgery, independent of changes in body adiposity, seems to be a good strategy to improve glucose homeostasis in pre-diabetic and diabetic experimental rodents and patients (13,18). However, the effects of DJB intervention upon the morphofunction of the endocrine pancreas are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…This effect may contribute to the normalization of islet and β-cell percentage per pancreas section in the HyO pancreas, contributing to normalize the β-cell secretory capacity. In addition, the improvement in hyperinsulinemia and insulin sensitivity in HyO DJB rats (18), may also be involved in such process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation